Why Does Education Increase Voting? Evidence from Boston’s Charter Schools - Cohodes, Sarah R.; Feigenbaum, James J. (The Review of Economics and Statistics, 2025)
Abstract Americans with more education vote more, but we know little about whether this effect on civic participation arises from educational quality or quantity. Using admissions lotteries at Boston charter schools, we find that charter attendance boosts voter participation, substantially increasing voting in the first presidential election after a student turns 18 by six percentage points from a baseline of 35 percent. This effect operates through increased turnout, as there is no increase in registration. Rich data enable us to explore multiple potential channels of this voting impact. Our evidence suggests that charters increase voting by increasing noncognitive skills.